Решим два дискриминанта:
x²+11x-12=0
a=1 b=11 c=-12
D=b²-4ac=> 11²-4*1*(-12) = 121+48 = 169 = 13² => 2 корня
x =
x₁ =
x₂ =
x²+14x+24=0
a=1 b=14 c=24
D=b²-4ac=> 14²-4*1*24 = 196-96 = 100 = 10² => 2 корня
Получаем:
Решим два дискриминанта:
x²+11x-12=0
a=1 b=11 c=-12
D=b²-4ac=> 11²-4*1*(-12) = 121+48 = 169 = 13² => 2 корня
x =![\frac{-b+-\sqrt{D} }{2a}](/tpl/images/0126/9634/c252a.png)
x₁ =![\frac{-11+13}{2} = 1](/tpl/images/0126/9634/5e3e1.png)
x₂ =![\frac{-11-13}{2} = -12](/tpl/images/0126/9634/2da66.png)
x²+14x+24=0
a=1 b=14 c=24
D=b²-4ac=> 14²-4*1*24 = 196-96 = 100 = 10² => 2 корня
x =![\frac{-b+-\sqrt{D} }{2a}](/tpl/images/0126/9634/c252a.png)
x₁ =![\frac{-14+10}{2} = -2](/tpl/images/0126/9634/7ad53.png)
x₂ =![\frac{-14-10}{2} = -12](/tpl/images/0126/9634/57c10.png)
Получаем:![\frac{(x-1)(x+12)}{x(x+2)(x+12))} = \frac{(x-1)}{x(x+2)}](/tpl/images/0126/9634/0bbad.png)